STUDY PENGARUH PARAMETER PEMOTONGAN TERHADAP GEOMETRI GERAM PADA PEMESINAN LAJU TINGGI, KERAS DAN KERING - Berta br Ginting (Jurnal Dinamis, 2014)
ABSTRACTIn this research, the material of AISI 4140 at 55 HRC was cut using CBN tool in high speedmachining, hard and dry machinery process. The chips, as the result of the whole condition ofthe cutting are observed morphologically and measured geometrically in the case of thethickness.The method used in this research is incremental experiment done in every segmentperformed in the certain cutting condition. In this case, the varieties of cutting: the speed cutting(V) (m/min), the feed (f) (mm/rev) and the depth of cutting c (mm) are performed.The result shows that the morphology of the chips formed have the geometrical featuresuch as saw-tooth; the higher the cutting speed (V), the thickness of the chip after the cutting(hc) tends to decrease and the distance between the edges of the saw (δ) tends to increase.Meanwhile the feed parameter (f) and the depth of the cutting (a) is in reverse with the speed ofcutting (V) ; the higher the feed (f) and the depth of the cutting (a), the thickness of the chip aftercutting (hc) tends to decrease.Keywords: the cutting parameter, geometrical chip,high- speed machining, hard machining,dry machining.